(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The main building material that can’t be ignored even it’s weak in tension and lead to various environmental problems during it’s production is concrete. Properties of concrete can be enhanced using fibre in concrete. Using fibre from waste of plastic in concrete to some percentage increases strength as well as durability of concrete and solve disposal problems of plastic waste in environment. From electronic waste Polyvinyl chloride cables (PVC) are used as fibre and from polypropylene (PP) packing bag of cement are used as fibre in concrete. Both are used in 0%, 0.25%, 0.50%, 0.75% and 1% by weight of cement in concrete. Fresh and harden properties for both concrete with polypropylene fibre and with electronic waste fibre is determined and hybrid of optimum values calculated is used in a single mix and compressive strength is calculated. Results show that 0.75% and 0.50% is optimum value of concrete with electronic waste fibre and concrete with polypropylene fibre with 49% and 17.5% increase in concrete strength compared to normal concrete respectively and can be used in a single mixture. Concrete with hybrid of polypropylene fibre and electronic waste fibre shows enhancement of 56% in compressive strength. The hybrid of PPFRC and EFRC polypropylene fibre keep cracks small and e-waste fibre shows enhancement in mechanical properties.